Economic analysis of the impact of Turkey's renewable support mechanism on solar energy investment - Erdem, Murat; Gurturk, Mert (Elsevier Sci Ltd, 2025)
This analysis considers the effects of past and present renewable support mechanisms on solar energy investment in Turkey based on economic conditions. Changes in the costs of solar energy plants due to inflation over time, the effects of the formula coefficients presented, and the advantages/disadvantages compared to the previous program are presented. Due to current high interest rates and inflationary pressures, annual earnings from solar energy investments have been calculated to range from US$ 70,946 to US$ 138,893. The investment payback period varies between 6.2 and 12 years, while the total support amount is 122.59 cents (US$/kWh). We find that the economic policies have negatively affected the predictability and sustainability of solar energy investments. The results are relevant to policymakers and investors. Optimum energy policies are needed for sustainable energy development in Turkey and developing countries like Turkey.
Keywords: Sustainable energy; Economic analysis; Energy policy; Incentive programs; SPPs